Does corrective exercises influence the performance, posture, range of motion and shoulder pain of swimmers with upper crossed syndrome? Randomized clinical trial - Rezaei, H.; Gheitasi, M.; Hosseini, S. M. (BMC Sports Science, Medicine and Rehabilitation, 2025)
Background This study sought to evaluate the effect of corrective exercises on forward head angle, forward shoulder angle, thoracic kyphosis degree, range of motion, and shoulder pain in elite front crawl swimmers presenting with upper crossed syndrome.